2018
DOI: 10.3390/su10093275
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Comprehensive Key Criteria of Sustainable Development for Traditional Manufacturing in Taiwan

Abstract: The traditional manufacturing industry has suffered from changing global demands and rapid technology upgrades. It is critical to incorporate innovation into contemporary manufacturing for sustainable development. A comprehensive interpretation of the determinants and directions of technical change is greatly needed. Therefore, this study aims to explore innovative applications that can enhance the value of manufacturing and examine the key factors associated with these innovations. In this paper, three tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…In terms of green development, Li L. et al [ 54 ] analyzed the impact of green innovation on the development of highly energy-consuming industrial enterprises in China. (3) In terms of innovation development, Lee Z. et al [ 55 ] reported that the traditional manufacturing industry should focus on design and innovation, which can ensure the development of manufacturing enterprises. Lee H. et al [ 56 ] found that innovative technology affects the productivity of the manufacturing industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of green development, Li L. et al [ 54 ] analyzed the impact of green innovation on the development of highly energy-consuming industrial enterprises in China. (3) In terms of innovation development, Lee Z. et al [ 55 ] reported that the traditional manufacturing industry should focus on design and innovation, which can ensure the development of manufacturing enterprises. Lee H. et al [ 56 ] found that innovative technology affects the productivity of the manufacturing industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lee et al believe that manufacturing should focus on innovation. This can not only improve manufacturing competitiveness, but also promote the sustainable development of traditional manufacturing [47]. Lee et al found that the innovation effect dominates the productivity of the Korean manufacturing industry [48].…”
Section: Motivation Of Manufacturing Competitivenessmentioning
confidence: 99%
“…In terms of technology, Lee et al reported that the traditional manufacturing industry should focus on design and innovation to ensure the development of manufacturing enterprises [36]. Lee H et al found that innovative technology affects the manufacturing industry's productivity, and the development of the manufacturing industry can be ensured through the improvement of innovative technology [37].…”
Section: Drivers Of Industry Transformationmentioning
confidence: 99%